The Role of Digital Marketing as a Tool for Creating and Sustaining Competitive Advantage in the Pharmaceutical Market in Lebanon - Bayoun, Dana (Digital Repository of Theses, 2024)
Introduction: Digital marketing practices have evolved critical tactics for promoting competitiveness and customer engagement in the pharmaceutical sector in Lebanon. The thesis examines the present status of digital marketing practices, and how companies are shifting from traditional marketing strategies towards including digital strategies covering the involvement, advantages, and challenges of these strategies for Lebanese pharmaceutical companies. Purpose: The primary goal is to investigate and analyze the Strategic implication of digital marketing adoption and the level of readiness for pharmaceutical firms in Lebanon. This research focused on the ability for readiness in terms of human and organizational difficulties in preparing and optimizing digital marketing techniques in the sector. Research methods: A mixed-methods design was employed to capture the complexity and variety of stakeholder perspectives. Study participants were interviewed, and surveys were conducted with coding and readiness assessment. The results were expected to provide detailed insights into an organization’s preparedness, skill gaps, and regulatory issues that affect the implementation of digital marketing. Findings: The analysis focused on the complexity and lack of readiness for a full transformation into the digital era. Skill gaps, regulatory challenges, and uncertainty in organizational responses were highlighted. However, a clear pathway towards success was demonstrated. This involves a step-by-step approach towards transformation, understanding that many aspects are affected by various limitations. Implications: The study provides helpful insights for the transformation of the marketing landscape of pharmaceutical companies in Lebanon. It also highlights the critical recommendations and points towards how the transition should be conducted. Strategic recommendations include targeted investments in internal initiatives to address skill deficits, the implementation of customer-centric engagement strategies leveraging digital platforms for customer communication and engagement, and advocacy for regulatory reforms to facilitate compliant and innovative digital marketing practices. Conclusion: this thesis contributes to academic research coupled with practical insights by emphasizing the imperative for strategic adaptation, continuous training, and regulatory reform to capitalize on the transformative potential of digital marketing in the Lebanese pharmaceutical context. By embracing digital tools strategically, pharmaceutical companies can enhance market competitiveness, optimize resource utilization, and adopt sustainable growth in evolving industry dynamics.